Cosmopolitanism: Religion and kinship among young people in south-western Sydney. (June 2014) - Turner, Bryan S.; Halse, Christine; Sriprakash, Arathi
Debates about globalization have been accompanied by considerable critical assessment of the notion of cosmopolitanism. The upsurge in travel, trade, communication, and resettlement among non-elite individuals and groups has raised questions about the nature and form of 'bottom-up' or 'vernacular' cosmopolitanism. This article explores the ways in which the experiences of a group of young people (12–15 years of age) in south-western Sydney contribute to shared practices of membership in a culturally differentiated society. On one level, these young people display a de facto vernacular cosmopolitanism through familial experiences of migration. However, the article shows how these young people often move within socially and culturally bounded communities defined by ethnicity, language, socio-economic status, shaped by desires for safety, support and belonging, and maintained by propinquity, religion and the persistence of traditional expectations and patterns around gender and inter-marriage.